Pengaruh Program Pemutihan Denda Pajak Kendaraan Bermotor, Pembebasan Bea Balik Nama dan Sosialisasi Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada UPT. Samsat Medan Utara - Rezeilina, Diana; Dalimunthe, Hasbiana (Innovative: Journal Of Social Science Research, 2024)
Taxpayers who have complied with all provisions of applicable tax laws and regulations, as well as their rights and obligations correctly and acceptably, are considered compliant. The purpose of this study was to determine the steps that have been taken in the context of nationalizing motor vehicle tax in accordance with the provisions of the Motor Vehicle Tax Law in North Sumatra, as well as to reduce motor vehicle tax fines and eliminate motor vehicle transfer fees. This quantitative analysis examines whether taxpayers have fulfilled their rights and responsibilities Based on the provisions of applicable tax laws and regulations, it is considered to apply further. Efforts to reduce motor vehicle tax sanctions, eliminate motor vehicle transfer fees and socialize motor vehicle taxes in accordance with the provisions of the UPT Shamsat Law. This study uses a survey methodology and is more quantitative. The sampling technique used with a total of 100 respondents is cross-sectional sampling. In this study, the multiple linear regression analysis method was used as a data analysis method using IBM SPSS software, classical hypothesis testing and descriptive statistical tests. The results of this study indicate that the tax socialization program, exemption from motor vehicle transfer taxes and reduction of motor vehicle tax sanctions can increase the interest of motor vehicle taxpayers to pay taxes at the UPT. Samsat North Sumatra